2015
DOI: 10.1523/jneurosci.4560-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Resting-State Activity Demonstrates Markers of Normalcy in Children with Prenatal or Perinatal Stroke

Abstract: Children who sustain a prenatal or perinatal brain injury in the form of a stroke develop remarkably normal cognitive functions in certain areas, with a particular strength in language skills. A dominant explanation for this is that brain regions from the contralesional hemisphere "take over" their functions, whereas the damaged areas and other ipsilesional regions play much less of a role. However, it is difficult to tease apart whether changes in neural activity after early brain injury are due to damage cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
(4 reference statements)
0
22
0
1
Order By: Relevance
“…In the current study, we conducted a large parameter space exploration with TVB, simulating BOLD fMRI and electrophysiological neural signals for 50 individual human brains. TVB has previously been used to study how neural networks behave in healthy and diseased states (8,10,13,18,21,26). Here, we assert that goodness-of-fit of simulated to empirical data converge at a particular parameter set across multiple tenets of the EEG and fMRI signal, and that there are reliable inter-individual differences in biophysical parameters that lead to optimal functioning.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the current study, we conducted a large parameter space exploration with TVB, simulating BOLD fMRI and electrophysiological neural signals for 50 individual human brains. TVB has previously been used to study how neural networks behave in healthy and diseased states (8,10,13,18,21,26). Here, we assert that goodness-of-fit of simulated to empirical data converge at a particular parameter set across multiple tenets of the EEG and fMRI signal, and that there are reliable inter-individual differences in biophysical parameters that lead to optimal functioning.…”
Section: Discussionmentioning
confidence: 92%
“…In a second set of simulations, we explored a narrower range of global coupling and reproduced alpha frequency (8)(9)(10)(11)(12)(13)(14)(15) Hz) oscillations in the neural signal, a characteristic feature of human empirical EEG (37,38), which has previously been modelled as a function of global coupling in MEG (30). Here, it was shown that transmission delays and global cortical coupling affect the mean power in an MEG model, and the best model fit was found in the alpha band power.…”
Section: Role Of Biophysical Parameters For Frequency and Alpha Bimodmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, an early childhood stroke that affects immature connections might have a stronger impact on functional reorganization than a stroke that affects more mature networks [29]. However, there exists also the hypothesis that damaged areas continue to support the performance of tasks involving them and the typical functional connections of these regions play an important role in preservation of normalcy after early perinatal stroke [52]. In our study significant changes in DMN and especially in the posterior precuneus part of DMN, which is the main hub within DMN, were found in the children with AIS who had also serious cognitive problems.…”
Section: Discussionmentioning
confidence: 99%